Epigenetic Control of Osteogenic Lineage Commitment - Montecino, Martin; Carrasco, Margarita E.; Nardocci, Gino (Frontiers in Cell and Developmental Biology, 2021)
Within the eukaryotic nucleus the genomic DNA is organized into chromatin by stably interacting with the histone proteins as well as with several other nuclear components including non-histone proteins and non-coding RNAs. Together these interactions distribute the genetic material into chromatin subdomains which can exhibit higher and lower compaction levels. This organization contributes to differentially control the access to genomic sequences encoding key regulatory genetic information. In this context, epigenetic mechanisms play a critical role in the regulation of gene expression as they modify the degree of chromatin compaction to facilitate both activation and repression of transcription. Among the most studied epigenetic mechanisms we find the methylation of DNA, ATP-dependent chromatin remodeling, and enzyme-mediated deposition and elimination of post-translational modifications at histone and non-histone proteins. In this mini review, we discuss evidence that supports the role of these epigenetic mechanisms during transcriptional control of osteoblast-related genes. Special attention is dedicated to mechanisms of epigenetic control operating at the Runx2 and Sp7 genes coding for the two principal master regulators of the osteogenic lineage during mesenchymal stem cell commitment.